Associations between domain-specific physical activity, sedentary behavior, and binge drinking among adults in the United States and China: evidence from a cross-sectional study, daily tracking, and randomized controlled trial - Liu, Zhuoxiao; Huo, Chiwei; Zhang, Xiaoling (Frontiers in Public Health, 2025)
BackgroundBinge drinking is linked to a range of diseases and has become a global public health concern. Engaging in physical activity may help reduce the prevalence of binge drinking and excessive alcohol consumption. However, the association may vary depending on the type of physical activity. This study aimed to investigate the association between different types of moderate-to-vigorous physical activity and binge drinking.Materials and methodsThis study included: (1) a cross-sectional survey included 6,707 individuals aged 20 years and older from the NHANES database between 2015 and 2018 (3,473 men and 3,234 women). Physical activity was assessed using the Global Physical Activity Questionnaire, and binge drinking was assessed using the Alcohol Use Questionnaire (ALQ). Binary logistic regression analysis was performed. (2) Daily tracking surveys collected daily data on the duration of physical activity and alcohol consumption over eight consecutive days from 80 individuals, resulting in 640 valid self-reported data points, which were analyzed using a generalized linear mixed-effects model. (3) A randomized controlled trial included 40 participants, randomly divided into a control group (20 individuals) and an experimental group (20 individuals). The experimental group engaged in 4 weeks (28 days) of group square dance recreational physical activity, while the control group had no assigned tasks. Paired-sample t-tests and independent-sample t-tests were used for analysis.ResultsA cross-sectional survey revealed work physical activity was positively associated with binge drinking (p < 0.001; OR = 1.50; 95%CI: 1.30–1.75). Transportation physical activity was positive associated with binge drinking (p = 0.002; OR = 1.30; 95%CI: 1.10–1.53). In contrast, recreational physical activity was negatively associated with binge drinking (p < 0.001; OR = 0.68; 95%CI: 0.58–0.79). Daily tracking surveys have externally validated the association between work-related physical activity and alcohol abuse (β = 0.002, p < 0.001). The association between transportation physical activity and alcohol abuse (β = 0.014, p < 0.001). A randomized controlled trial strengthened the association between recreational physical activity and alcohol abuse, showing that an association between increased recreational physical activities and reduced alcohol abuse (p < 0.001).ConclusionDifferent types of physical activity are associated with different patterns of binge drinking. Therefore, when using physical activity as a measure to control binge drinking, it is necessary to pay attention to the type and duration of physical activity.